2015
DOI: 10.1039/c4ra16968a
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic oxidation of 5-hydroxymethylfurfural (HMF) effectively catalyzed by a Ce0.8Bi0.2O2−δ supported Pt catalyst at room temperature

Abstract: The oxidation of 5-hydroxymethylfurfural (HMF) to 2,5-furandicarboxylic acid (FDCA) was efficiently catalyzed when Pt nanoparticles (NPs) were supported onto a Ce 0.8 Bi 0.2 O 2Àd solid solution. 98% yield of FDCA was achieved within 30 min at room temperature and the catalyst was reused five times without much loss of FDCA selectivity. It is the first report on the oxidation of HMF, an alcohol and an aldehyde, effectively catalyzed by a ceria-based material supported Pt catalyst. The individual properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 37 publications
4
55
1
Order By: Relevance
“…Similarly, Pt‐based catalysts have also shown higher catalytic performance for the oxidation reaction . Siankevich et al.…”
Section: Catalytic Oxidation Of Biomass‐derived Furfural and Hmf Overmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Pt‐based catalysts have also shown higher catalytic performance for the oxidation reaction . Siankevich et al.…”
Section: Catalytic Oxidation Of Biomass‐derived Furfural and Hmf Overmentioning
confidence: 99%
“…Similarly,P t-based catalysts have also shown higherc atalytic performance for the oxidation reaction. [206][207][208][209][210][211][212][213][214] Siankevich et al achieveda nefficient oxidation of HMF to FDCA over platinum nanoparticles coated with an imidazolium-based cross-linked polymeru sing oxygen as an oxidizing agent at 80 8Cu nder aqueous reaction conditions. [206] The study suggested that the counter anion of cationic polymer (chloride, BF 4 À ,P F 6 À ,b is(trifluoromethylsulfonyl)imide, hexanoate or laurateanions) affected the structure of Pt nanoparticles along with the surface electronic properties andt he catalytic activity.T he resultsinferred that bis(trifluoromethylsulfonyl)imide (weak nucleophilic anion) resulted in the highest reaction rates, which was assigned due to the weak interaction of polymer with the surface of nanoparticles and hence led to an ease access to the substrates.A nalogously,P tn anoparticles supported on functionalized carbon nanotubes (CNTs) have shown high performance towardsb ase-free aerobic oxidation of HMF to FDCA.…”
Section: Catalytic Oxidation Of Biomass-derived Furfural and Hmf Overmentioning
confidence: 99%
See 1 more Smart Citation
“…Other than Au catalysts, Pt‐, Ru‐ and Pd‐based catalysts were also reported in the oxidation of 5‐HMF. In this direction, Pt‐based catalysts have exhibited high efficiency for the complete oxidation of 5‐HMF to FDCA, however, in the presence of a strong base and high pressure of O 2 or air . For example, recently Han et al.…”
Section: Introductionmentioning
confidence: 99%
“…also reported in the oxidation of 5-HMF.I nt his direction, Ptbased catalysts have exhibited high efficiency for the complete oxidation of 5-HMF to FDCA, however,i nt he presenceo f as trong base and high pressure of O 2 or air. [39,[48][49][50][51][52][53][54][55] [55] On the other side, Ru catalysts howed only partial oxidation of 5-HMF to DFF at 110 8Cw ith high pressure of O 2 , 2.0 MPa, using organic solvents. [56,57] Similarly to Au, Pd catalysts also showed high activity towards the oxidation of alcohols and carbonyl compounds.…”
Section: Introductionmentioning
confidence: 99%